2022
DOI: 10.1186/s42269-022-00825-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, laboratory characteristics and risk factors for mortality of COVID-19 patients in a secondary hospital in Oman during the first wave of the SARS-CoV-2 pandemic

Abstract: Background The changing epidemiological profile of the COVID-19 pandemic and the uncertain clinical picture of patients characterise this ongoing and most challenging health event. Objectives To report clinical features, laboratory characteristics, and mortality risk factors among COVID-19 patients admitted to a secondary hospital in Oman. Methods A retrospective study for the first 455 patients admitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
5
5
0
Order By: Relevance
“…This study showed that the most common alterations were increased values of CRP, ferritin, D-dimer, reduced amount of CO2 in serum, and reduced lymphocyte count, and these could be considered as significant biomarkers for COVID-19 prognosis. These findings agree with recent national [ 15 ] and international studies [ 6 , 26 ]. Similar to our findings, Wang et al reported that increased values of CRP, D-dimer, ferritin, and troponin T and reduced lymphocyte count were the most frequent laboratory alterations that were highly associated with mortality [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This study showed that the most common alterations were increased values of CRP, ferritin, D-dimer, reduced amount of CO2 in serum, and reduced lymphocyte count, and these could be considered as significant biomarkers for COVID-19 prognosis. These findings agree with recent national [ 15 ] and international studies [ 6 , 26 ]. Similar to our findings, Wang et al reported that increased values of CRP, D-dimer, ferritin, and troponin T and reduced lymphocyte count were the most frequent laboratory alterations that were highly associated with mortality [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…Other uncommon symptoms were myalgia, difficulty in breathing, and sore throat. These findings agree with previous national [ 13 , 15 , 22 , 25 ] and an international study [ 2 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“… 13 Many types of research have proven that comorbidities, age, and abnormalities of numerous scientific biomarkers may be essential to apprehending the sickness severity. 14 , 15 Even though the clinical characteristics of the COVID-19 pandemic have been widely reported, the summary of changes in the common hematological variables that are observed in patients with various waves of COVID-19 infection is still not well investigated, the published laboratory findings of COVID-19 infection are collected from hospital-admitted patients at a single time point which limits our understanding of the dynamic hematological changes during the disease, clinical symptoms and severity of the disease is differing across a wave. 16 The consistency and difference of the hematological profiles of COVID-19 patients across waves remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%